Activation of the Surface of Cotton Fabrics for Chemical Metallization - Malik Sataev; Shayzada Koshkarbaeva; Kalamkas Amanbaeva; Perizat Abdurazova; Yerkebulan Raiymbekov (Challenges and Advances in Chemical Science Vol. 8, 2022)
It is proposed to use physical and chemical processes occurring in thin layers of copper (II) chloride solutions under the influence of electromagnetic solar rays of the visible spectrum to activate the surface of cotton fabrics prior to chemical nickel plating. It is demonstrated that in the presence of copper (II) chloride, the main component of the fabric, cellulose undergoes photo-oxidation. This interaction results in the formation of well-bonded copper monochloride. Copper monochloride is transformed into copper and copper phosphide during further processing of the fabric with phosphine gas. Copper phosphide functions as a catalyst in the chemical nickel plating process. This allows for the formation of an electrically conductive nickel-phosphorus coating on the surface of the fabric in conventional chemical nickel plating electrolytes. It has also been discovered that when individual sections are screened, the processes that lead to the formation of copper monochloride do not occur. This enables the fabric to be metallized selectively.